2003
DOI: 10.1159/000069479
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Relationships between Various Domains of Hearing Aid Provision

Abstract: Various inventories have been developed to quantify the success of hearing aid provision. Though numerous parameters including initial measures (hearing disability, handicap) or ‘outcome measures’ (e.g. benefit, satisfaction and usage) are recorded, relationships and interactions among them are still unclear. A study applying a questionnaire addressing 11 domains relevant to amplification was conducted in order to generate different psychometric models with the AMOS© software package for structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…A study attempted to model the relationships between various domains found that hearing-aid usage among experienced users were not signifi cantly related to benefi t and satisfaction (Meister et al, 2003), yet perceived benefi t was infl uential on satisfaction. A review of 45 studies also reported of mixed fi ndings on the satisfaction of hearing-aid infl uence on its usage, though higher usage was evident to increase satisfaction (Wong et al, 2003).…”
Section: Expectation Self-perceived Benefi T Satisfactionmentioning
confidence: 99%
“…A study attempted to model the relationships between various domains found that hearing-aid usage among experienced users were not signifi cantly related to benefi t and satisfaction (Meister et al, 2003), yet perceived benefi t was infl uential on satisfaction. A review of 45 studies also reported of mixed fi ndings on the satisfaction of hearing-aid infl uence on its usage, though higher usage was evident to increase satisfaction (Wong et al, 2003).…”
Section: Expectation Self-perceived Benefi T Satisfactionmentioning
confidence: 99%
“…Nach Meister et al [17] besteht zwar grundsätzlich ein Zusammenhang zwischen der Bedeutung von Hörgeräteeigen-schaften und der Erwartungshaltung. Die Relation ist aber nicht sehr eng, sodass die Erwartungen durchaus auch von anderen Einflüssen bestimmt werden können.…”
Section: Erwartungen Bezüglich Hörgeräteeigenschaftenunclassified